Health Insurance Literacy Perceptions and the Needs of a Working-Class Community - Rishtya Kakar; Ryan M. Combs; Malea Hoepf Young; Nida Ali; Baraka Muvuka (SLACK Incorporated, 2022)
Background: Despite increases in the number of insured Americans, consumers continue to face barriers in accessing care. Low levels of health insurance literacy (HIL) are associated with suboptimal use of health insurance coverage. There remains a need to further contextualize the relationship between HIL and access to care, especially among insured working-class people. Objective This study was conducted to understand the pathways through which HIL affects health care decision-making and access to care in an urban working-class population. Methods: Using a qualitative descriptive approach, we conducted five focus groups with 45 adult residents of South Louisville, Kentucky. The questions explored participants' experiences of insurance enrollment, use, and health care system navigation, as well as their perceptions and needs regarding accessing health insurance information. Using inductive thematic analysis, transcripts were open coded independently by team members, a focused coding framework was agreed upon, and emergent themes were identified through constant comparison techniques. Key Results: Most participants placed high value on their insurance, considering it the most important benefit employers offer. Despite having adequate HIL, most participants expressed frustration with the amount of time and effort they spent to determine the best insurance plan, obtain covered health services, and settle claims, often with ineffective results. Despite having insurance, cost considerations influenced many participants' decisions to accept certain tests or treatments, in some cases resulting in delayed or foregone care. Conclusions: The findings of this qualitative study indicate that obtaining health care is strongly influenced both by the individual context of HIL knowledge, experience, and life circumstances, and by the structural context of the complex, bureaucratic, and costly health care system. Interventions to improve HIL should include practical examples and real-life scenarios, because HIL gained from experiential narratives was the most useful in navigating the health care system.[HLRP: Health Literacy Research and Practice. 2022;6(2):e61-e69.] Plain Language Summary: By conducting focus groups with a working-class population, this study contextualizes the pathways through which HIL affects consumers' health care decision-making and access to care. Findings demonstrate that obtaining health care is strongly influenced both by the individual context of HIL knowledge, experience, and life circumstances, and by the structural context of the complex, bureaucratic, and costly health care system.